2019
DOI: 10.1016/j.energy.2018.10.079
|View full text |Cite
|
Sign up to set email alerts
|

A novel system for large-scale storage of electricity as synthetic natural gas using reversible pressurized solid oxide cells

Abstract: The ongoing reduction of greenhouse gas emissions entails increased use of intermittent renewable energy technologies such as wind and solar. This raises the need for costeffective and efficient electricity storage. In particular seasonal variations in supply and demand will require tremendous storage capacity. In this paper we present a truly largescale electricity storage system which uses pressurized reversible solid oxide cells combined with catalytic reactors to store electricity as synthetic natural gas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…However, at high pressure (15 bar), higher efficiencies of up to 70% were reported by them. In another similar study, Butera et al (2019) reported that during the reversible operation of solid oxide cells at higher pressures, the RTE can be further increased to 80% through proper adjustment of the H/C ratio of the gases being purged into the cell during both electrolysis and fuel-cell modes. From preliminary energy balance calculations and considering minimal balance of plant requirements, it can be stated that in situ methanation in SOECs is the most efficient yet relatively cheaper option for methane synthesis as well as hydrogen recovery.…”
Section: Energy Efficiency Of Methane Synthesis Via Different Electromentioning
confidence: 98%
“…However, at high pressure (15 bar), higher efficiencies of up to 70% were reported by them. In another similar study, Butera et al (2019) reported that during the reversible operation of solid oxide cells at higher pressures, the RTE can be further increased to 80% through proper adjustment of the H/C ratio of the gases being purged into the cell during both electrolysis and fuel-cell modes. From preliminary energy balance calculations and considering minimal balance of plant requirements, it can be stated that in situ methanation in SOECs is the most efficient yet relatively cheaper option for methane synthesis as well as hydrogen recovery.…”
Section: Energy Efficiency Of Methane Synthesis Via Different Electromentioning
confidence: 98%
“…The capability of such a reversible operation makes rSOC very attractive for grid balancing or decentralized grid independent energy source application. System modelling results showed that a round trip efficiency (power-to-gas-to-power) of up to 80% could be achieved by combing pressurized operation and storing the electricity as chemical bound energy in CH 4 (1). rSOC system with 50 kW SOFC and 120 kW SOEC has been demonstrated (5).…”
Section: Introductionmentioning
confidence: 99%
“…If the biofuel produced is methane, there is an additional benefit of SOC pressurization, as it is possible to have internal methanation inside a state-of-the-art SOC if carbonaceous gasses are supplied to the SOC (Butera et al, 2019;Jensen et al, 2015Jensen et al, , 2017. This can be achieved by sending humidified syngas to the SOC (Fig.…”
Section: Pressurization and Internal Methanation In Solid Oxide Cellsmentioning
confidence: 99%
“…Simplified flowsheet of a methane-producing system based on pressurized gasification and pressurized SOC with internal methanation. Note: part of the syngas bypasses the SOEC to allow (1) a high H/C ratio in the SOEC, thereby avoiding equilibrium carbon formation (Butera et al, 2019), and (2) having the optimal ratio between H2, CO and CO2 for methane synthesis before the synthesis reactor (Butera et al, 2019). If other biofuels than methane are produced, it would still be possible to feed a pressurized SOEC with syngas, but it requires the use of SOECs without nickel in the fuel electrode, as nickel catalyses methane synthesis.…”
Section: Pressurization and Internal Methanation In Solid Oxide Cellsmentioning
confidence: 99%